MEDIATORS OF INFLAMMATION IN LEUKOCYTE LYSOSOMES : VI. PARTIAL PURIFICATION AND CHARACTERIZATION OF A MAST CELL-RUPTURING COMPONENT - Seegers, Winnifred (The Rockefeller University Press, 1966)
The mast cell-rupturing component present in the lysosomes of rabbit exudate PMN neutrophil leukocytes has been identified and some of its physical and chemical properties have been described. The active agent is a low molecular weight (1200 to 2400) polypeptide containing a relatively large proportion of the basic amino acid, arginine. It is thermostable and dialyzable, and does not cause contraction of the isolated guinea pig ileum. The mast cell-rupturing activity of the agent is destroyed by trypsin. A second permeability factor with a larger molecular weight is present in crude extracts of PMN granules. Although this substance does not lyse mast cells, it is capable of evoking delayed permeability responses in rabbit skin.